Scaffolding strategy in the process of writing to improve the students' writing ability - Ary Setya Budhi Ningrum (Kementerian Agama RI Direktorat Jenderal Pendidikan Islam Direktorat Pendidikan Tinggi Islam, 2012)
tr,1/nr,c.1